A review on conceptualization and dimensions of safety climate - Yeong, Sook Shuen (2014)
Recent development in industrialization and global economy has contributed to the increased number of workplace injuries and accidents. Safety culture has been seen as a central medium to curb the worrying trend of workplace accidents. The term of safety culture has emerged from the Chernobyl nuclear disaster in 1986 and the concept has been widely used until today. However, the conceptualization of safety culture suffers from several major drawbacks such as no definite understanding of how safety culture being defined and measured. This paper hypothesized that higher levels of safety culture in the workplace will display lower numbers of accidents. Due to this concern, this paper seeks to provide a clear conceptualization of safety culture, dimensions used to measure it and common research methodology used in the previous safety research.